2017
DOI: 10.1177/0145721717697245
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of “Struggling to Live Life”

Abstract: Purpose The purpose of the study was to explore and describe perceptions and experiences of young adults with type 1 diabetes mellitus (T1DM) living in Appalachia, Tennessee. Methods Qualitative descriptive analysis of in-depth interviews of 9 young adults (male = 3, female = 6) 18 to 30 years of age living in Appalachian counties in Tennessee provided the basis of identifying the salient concerns from the perspective of this diverse group related to living daily with T1DM. Data analysis was facilitated by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 9 publications
9
44
0
Order By: Relevance
“…The results revealed that participants were worried and sometimes scared of having low blood glucose. Related to low blood glucose, the participants were anxious about losing control of their bodies, the situation or even die, which also was shown in prior studies (Abdoli et al, ; Zoungas et al, ). The results pointed out the participants fear of being a burden to other people, for example, if they might end up in need of assistance.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The results revealed that participants were worried and sometimes scared of having low blood glucose. Related to low blood glucose, the participants were anxious about losing control of their bodies, the situation or even die, which also was shown in prior studies (Abdoli et al, ; Zoungas et al, ). The results pointed out the participants fear of being a burden to other people, for example, if they might end up in need of assistance.…”
Section: Discussionsupporting
confidence: 72%
“…To avoid such situations, participants described maintaining their blood sugar higher than usual, some for special occasions and some for a longer period. Previous studies (Abdoli et al, ; Cryer, ; Martyn‐Nemeth et al, ) show that fear of hypoglycaemia is one of the major limiting factors in achieving optimal blood glucose control for persons living with T1D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who preferred not to reveal their identity, explained that web-based forums were valuable arenas for exchanging experiences. According to Balfe et al [13] and Abdoli, Hardy & Hall [5], participants in their studies expressed the view that other people with T1D had empathy and understanding for their experiences. It was also a positive experience for young adults when healthcare personnel recognized them, for example, by knowing their name.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, young adults try to live as normally as possible with the illness [4]. Abdoli et al [5] stated that young adults with T1D struggle to grow and take on more responsibility of diabetes management. Earlier studies [6][7][8] have shown that managing daily life with a long-term illness increases the importance of support from family, friends and healthcare personnel.…”
Section: Introductionmentioning
confidence: 99%